Effects of bacterial fertilizer and soil amendment on Spuriopinella brachycarpa (Kom.) Kitag. growth and soil microbiota - Zou, Yue; Zou, Yan; Yang, Baiming; Qiao, Jianlei; Liu, Shuang; Zhao, Chunbo; Shi, Kun; Yu, Yue; Li, Shuang; Chen, Shanshan (Frontiers in Microbiology, 2025)
IntroductionSpuriopinella brachycarpa (Kom.) Kitag. is a nutritious wild vegetable, but its quality deteriorates during artificial cultivation due to soil condition alterations. Microbial fertilizers and soil amendments hold promise for improving cultivation outcomes, yet their combined effects remain under - explored.MethodsA field experiment was conducted with seven treatments, including a control (CK) and six combinations of Trichoderma harzianum, Bacillus subtilis, and earthworm polysaccharide. Plant samples were analyzed for yield, quality, and root architecture, while soil samples were tested for fertility and microbial community characteristics.ResultsTreatments T3 (dual bacterial fertilizers) and T6 (dual bacterial fertilizers + soil amendment) significantly enhanced yield, nutritional quality, and root development. T6 also maintained high soil fertility and optimized the soil microbial community in terms of richness, diversity, and beneficial species abundance.DiscussionThe positive effects of T3 and T6 are likely due to the synergy between the bacterial fertilizers and the soil amendment, which improves nutrient cycling, soil structure, and microbial functions. However, the study has limitations, such as the need for long - term research and more in - depth exploration of microbial functions.